KONTRIBUSI TEORI KEPENTINGAN KELOMPOK DALAM STANDAR AKUNTANSI KEUANGAN (SUATU KAJIAN LITERATUR) - PUTRA ASTIKA, I.B. (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
In order to present useful financial report for economic decision making, regulation of accounting standard becomes important. Economic and politic conditions contribute heavily to regulator in creating, improving, and renewing accounting standard in a country. It means that accounting standard is not purely born from theory, but contributed by economic and politic conditions. Accounting standards dominantly derived from theory have failed. The standards have not accepted by business community and politicians or general stakeholders because not in line with their political will. Based on this situation, it would be right to say that accounting standard is a consensus dominantly supported by group interest theory.
Keywords: regulation, financial report, accounting standard, consensus